2021
DOI: 10.1186/s12961-021-00794-y
|View full text |Cite
|
Sign up to set email alerts
|

Is value-based payment for healthcare feasible under Ghana’s National Health Insurance Scheme?

Abstract: Background Effective payment mechanisms for healthcare are critical to the quality of care and the efficiency and responsiveness of health systems to meet specific population health needs. Since its inception, Ghana’s National Health Insurance Scheme (NHIS) has adopted fee-for-service, diagnostic-related groups and capitation methods, which have contributed to provider reimbursement delays, rising costs and poor quality of care rendered to the scheme’s clients. The aim of this study was to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“… [ 31 , 35 , 39 , 41 , 42 , 47–49 , 53 , 55 , 57 , 61 , 65 , 79 ] Provider opposition to being held accountable for outcomes they cannot control. [ 41 , 43 , 48 , 49 , 55 , 57 , 61 , 65 , 70 , 79 ] Provider reluctance or opposition to reform initiatives seeming to compromise their professional/ clinical autonomy or ethics. [ 31 , 33 , 37 , 39 , 52 , 53 , 55 , 57 , 69 , 80 ] Distrust due to previously failed reform attempts or between stakeholders (eg, care providers and government).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… [ 31 , 35 , 39 , 41 , 42 , 47–49 , 53 , 55 , 57 , 61 , 65 , 79 ] Provider opposition to being held accountable for outcomes they cannot control. [ 41 , 43 , 48 , 49 , 55 , 57 , 61 , 65 , 70 , 79 ] Provider reluctance or opposition to reform initiatives seeming to compromise their professional/ clinical autonomy or ethics. [ 31 , 33 , 37 , 39 , 52 , 53 , 55 , 57 , 69 , 80 ] Distrust due to previously failed reform attempts or between stakeholders (eg, care providers and government).…”
Section: Resultsmentioning
confidence: 99%
“… [ 31 , 33 , 37 , 39 , 52 , 53 , 55 , 57 , 69 , 80 ] Distrust due to previously failed reform attempts or between stakeholders (eg, care providers and government). [ 33 , 41 , 43 , 47 , 48 , 62 ] Reluctance due to difficulty/the inertia of providers to adjust to the new structure in healthcare. [ 14 , 47 , 52 , 61 , 74 ] Providers reluctance to adopt new payment models because they feel better familiar with the current one.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the geospatial diffusion, studies have also found the temporal diffusion of policies within the same country as the case of CBHIs which served as a learning precursor for the NHI in Ghana 36. This temporal diffusion also explains how Ghana’s fee exemption policy for maternal health initiated in 1963 was maintained over the years in a path-dependent manner 106. While policies are dominantly framed as diffusing from norm-setting agencies at global level to SSA following a rigorous evidentiary process, exceptions exist where country level implementation influenced global policy.…”
Section: Methodsmentioning
confidence: 98%
“…36 This temporal diffusion also explains how Ghana's fee exemption policy for maternal health initiated in 1963 was maintained over the years in a path-dependent manner. 106 While policies are dominantly framed as diffusing from norm-setting agencies at global level to SSA following a rigorous evidentiary process, exceptions exist where country level implementation influenced global policy. Pragmatic considerations influenced Malawi to adopt Option B+for Prevention of Mother To Child Transmission for HIV/AIDS ahead of WHO recommendations and guidelines; a policy that rapidly diffused to other countries in the absence of normative (formalised) guidelines from WHO.…”
Section: Transnational and National Policy Diffusionmentioning
confidence: 99%